Efeitos da cobrança pelo acesso à saneamento básico sobre o consumo de alimentos e assistência à saúde: evidências da importância da tarifação social para o desenvolvimento humano - Tomaz, Nicolas Cáiron (2020)
This master’s thesis investigated how the exemption from charging for access to sanitation impacts household spending on food and health. Data from Pesquisa de Orçamento Familiar de 2008 e 2009 (POF 2008-2009) from Instituto Brasileiro de Geografia e Estatística (IBGE) were used. The relationship between sanitation, food and health can be understood in the context of human development established by the literature. For the empirical analysis, the impacts of exemption from charging for access to water and sanitation services were estimated on household expenditure on food, health care and other categories of expenditure. The results found corroborate the importance of defining social rate systems (subsidies) for human development, in view of their positive and significant effect on food consumption. This relationship reveals that social rate can be used as a public policy to promote human development when applied to the poorest people.